Expression patterns of mRNAs for methanotrophy and thiotrophy in symbionts of the hydrothermal vent mussel Bathymodiolus puteoserpentis - Wendeberg, Annelie (Nature Publishing Group, 2012)
The hydrothermal vent mussel Bathymodiolus puteoserpentis (Mytilidae) from the Mid-Atlantic Ridge hosts symbiotic sulfur- and methane-oxidizing bacteria in its gills. In this study, we investigated the activity and distribution of these two symbionts in juvenile mussels from the Logatchev hydrothermal vent field (14°45′N Mid-Atlantic Ridge). Expression patterns of two key genes for chemosynthesis were examined: pmoA (encoding subunit A of the particulate methane monooxygenase) as an indicator for methanotrophy, and aprA (encoding the subunit A of the dissimilatory adenosine-5′-phosphosulfate reductase) as an indicator for thiotrophy. Using simultaneous fluorescence in situ hybridization (FISH) of rRNA and mRNA we observed highest mRNA FISH signals toward the ciliated epithelium where seawater enters the gills. The levels of mRNA expression differed between individual specimens collected in a single grab from the same sampling site, whereas no obvious differences in symbiont abundance or distribution were observed. We propose that the symbionts respond to the steep temporal and spatial gradients in methane, reduced sulfur compounds and oxygen by modifying gene transcription, whereas changes in symbiont abundance and distribution take much longer than regulation of mRNA expression and may only occur in response to long-term changes in vent fluid geochemistry.